Aging Research Using Mouse Models. Issue 2 (1st June 2015) - Ackert‐Bicknell, Cheryl L.; Anderson, Laura C.; Sheehan, Susan; Hill, Warren G.; Chang, Bo; Churchill, Gary A.; Chesler, Elissa J.; Korstanje, Ron; Peters, Luanne L.
Abstract : Despite the dramatic increase in human lifespan over the past century, there remains pronounced variability in "health‐span, " or the period of time in which one is generally healthy and free of disease. Much of the variability in health‐span and lifespan is thought to be genetic in origin. Understanding the genetic mechanisms of aging and identifying ways to boost longevity is a primary goal in aging research. Here, we describe a pipeline of phenotypic assays for assessing mouse models of aging. This pipeline includes behavior/cognition testing, body composition analysis, and tests of kidney function, hematopoiesis, and immune function, as well as physical parameters. We also describe study design methods for assessing lifespan and health‐span, and other important considerations when conducting aging research in the laboratory mouse. The tools and assays provided can assist researchers with understanding the correlative relationships between age‐associated phenotypes and, ultimately, the role of specific genes in the aging process. © 2015 by John Wiley & Sons, Inc.